College Electronic Voting Environment (CEVE) - Mwesigwa, Ezra; Bagarukayo, Emily (IEEE, 2015)
The traditional usage of the pen and ballot paper to elect new student leaders at the College of Computing and Information Sciences (CoCIS), Makerere University has been rendered ineffective due to various recurring errors. Long tedious queues, ballot stuffing allegations, voting multiple times, high operational expense, depict the voting process at CoCIS. The study therefore aimed at developing an electronic voting environment to address these challenges. We reviewed literature and studied the current voting process to attain the user and system requirements. The key design tools were Entity Relationship Diagrams (ERDs), Context Diagrams and use case diagrams. Through extensive user involvement and research, we developed and implemented using Hypertext Preprocessor (PHP) and Structured Query Language (MySQL), tested and validated a fully functioning system to solve the challenges. The College Electronic Voting Environment (CEVE) automates the current manual voting process such that voters register and cast votes online from anywhere as long as they have internet access.
Keywords: College; Electronic Voting; Voting Environment